GAMBARAN PENGOLAHAN LIMBAH CAIR DALAM PENCEGAHAN PENCEMARAN LINGKUNGAN DI RSUD SOLOK SELATAN - Armein Lusi Zeswita; Gustina Indriati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Liquid waste is the residue from a business or activity in the form of liquid that is disposed of into the environment and can reduce environmental quality. Hospital waste is not a common type of waste. Waste generated by hospitals has more complex characteristics, this is because hospital waste contains pathogenic microorganisms, toxic chemicals, and radioactivity. The purpose of this study was to find out how the description of wastewater treatment in South Solok Hospital in 2022. This type of research is descriptive with a qualitative approach, namely by explaining the wastewater treatment system of South Solok Hospital. The results of this study found that the sources of wastewater from the Solok Selatan Hospital came from various rooms including the canteen, kitchen, bathroom, nurse's room, operating room, isolation room, polyclinic, pharmacy room, midwifery and laboratory. The results of the liquid waste laboratory test from the Solok Selatan Hospital have met the quality standard value of liquid waste.